The Relationship Between Internal Locus of Control and Altruistic Behavior Among Students of the Faculty of Teacher Training and Education, Syiah Kuala University, Banda Aceh - Islamiyah, Annisa Rizka; Barmawi, Barmawi; Ulfah, Marina; Cipta, Hendra (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
As students of the Faculty of Teacher Training and Education (FKIP), it is important to possess altruistic behavior. Those who choose to study in FKIP are individuals who aspire to become teachers. One of the main reasons people choose the teaching profession is their desire to help others, which reflects altruistic behavior. According to Stinnett (1968), the teaching profession is characterized as a vocation motivated by the need to help others rather than by financial gain. One of the factors influencing altruistic behavior is internal locus of control. This study aims to determine the relationship between internal locus of control and altruistic behavior among students of the Faculty of Teacher Training and Education (FKIP), Syiah Kuala University, Banda Aceh. The research employed a quantitative approach with a correlational method. The population consisted of 6,706 students, with a sample of 332 students selected using the simple random sampling technique. The instruments used in this study were the Internal Locus of Control Scale and the Altruistic Behavior Scale. Data analysis was conducted using the Pearson Product-Moment Correlation test. The results showed a positive and significant relationship between internal locus of control and altruistic behavior among FKIP students at Syiah Kuala University, with a Pearson correlation coefficient of r = 0.830 and a significance value of p = 0.000 (p < 0.05). This indicates that the higher the internal locus of control, the higher the level of altruistic behavior, and conversely, the lower the internal locus of control, the lower the altruistic behavior.